Answers

2014-07-27T16:58:46+08:00
(cot x - csc x)(cos x+1)
=( cos x/sin x - 1/sin x)(cos x + 1)      / cot x = cos x/sin x;  csc x = 1/sin x
=( cos x-1)/sin x)(cos x+ 1)
=  (cos² x-1)/sin x          /   ( cos x-1)(cos x+1) =  cos² -1
=  - sin² x/sin x              /  sin² x + cos² x = 1   or   cos² x -1 = -sin² x
=     -sin x
so        (cot x - csc x)(cos x+ 1) =  -sin x








0
thankyou po:) sobrang kailangan kupu kasi ito. godbless po
reverse pala :( why -sinx = (cot x - csc x)(cos x +1) ? solution for -sinx, please :(
2014-07-27T17:34:23+08:00
Look at this :D
I'm not actually sure with my answer since we were only taught the basics in trigonometry but I still hope this helps.

0